Managing vulvovaginal atrophy after breast cancer. Issue 4 (December 2018) - Sassarini, Jenifer; Perera, Mahesh; Spowart, Keith; McAllister, Kay; Fraser, Judith; Glasspool, Ros; Harrand, Rosie; Chitoni, Marina; Stallard, Sheila; Lumsden, Mary-Ann
Cancer treatment may result in loss of ovarian function through surgical removal of the ovaries, chemotherapy or radiation. While menopausal symptoms, such as hot flushes, night sweats, sleep disturbance, memory concerns and mood issues can be extremely bothersome to some women going through menopause naturally, women who undergo an induced menopause usually experience more sudden and severe symptoms. Pain and vaginal dryness can occur whether a woman has a sexual partner or not. In women with breast cancer, the aetiology of impaired sexual functioning, and lowered sexual desire, is often multifactorial, and may be related to physical and/or psychological reasons. Pain and vaginal dryness in women without a history of breast cancer can usually be safely treated with vaginal estrogens, in the form of a cream, pessary or ring, and simple lubricants or vaginal moisturisers. Safe usage of vaginal estrogen replacement therapy in breast cancer patients has not been studied within randomised clinical trials of long duration; the guidelines below reflect a clinical consensus.